The role of bile acid metabolism in the occurrence and development of NAFLD - Bing, Hao; Li, Yi-Ling (Frontiers in Molecular Biosciences, 2022)
Nonalcoholic fatty liver disease (NAFLD) has become one of the important causes of cirrhosis and liver cancer, resulting in a huge medical burden worldwide. Currently, effective noninvasive diagnostic indicators and drugs for NAFLD are still lacking. With the development of metabolomics technology, the changes in metabolites during the development of NAFLD have been gradually revealed. Bile acid (BA) is the main endpoint of cholesterol metabolism in the body. In addition, it also acts as a signaling factor to regulate metabolism and inflammation in the body through the farnesyl X receptor and G protein-coupled BA receptor. Studies have shown that BA metabolism is associated with the development of NAFLD, but a large number of animal and clinical studies are still needed. BA homeostasis is maintained through multiple negative feedback loops and the enterohepatic circulation of BA. Recently, treatment of NAFLD by interfering with BA synthesis and metabolism has become a new research direction. Here, we review the changes in BA metabolism and its regulatory mechanisms during the development of NAFLD and describe the potential of studies exploring novel noninvasive diagnostic indicators and therapeutic targets for NAFLD based on BA metabolism.